USE OF THE ANTIVIRAL DRUG «ARBIMECTIN» IN THE TREATMENT REGIMEN FOR CALICIVIRUS IN CATS - Zaykovskaya, O.; Zhexenayeva, A.; Zhakiyanova, M. (ЗКАТУ им. Жангир хана, 2024)
The article discusses the possibility of using the antiviral drug "Arbimectin" in the treatment regimen for cats suffering from a viral disease - calcivirus. Data are presented confirming the effectiveness of Arbimectin in all forms of calicivirus in cats. Some issues of the pharmacodynamics of Arbimectin in the treatment of intracellular viruses are considered. The given treatment regimen makes it possible to increase the effectiveness of calcivirus therapy in sick animals. The use of Arbimectin, which has the ability to penetrate into affected cells and block the synthesis of viral ribonucleic acid, significantly reduces the duration of the disease and mortality among cats. Arbimectin promotes a more complete release of the body from the virus, which is confirmed by a reduction in the time it takes for the viral antigen to be released from the body of animals. Studies have shown that the inclusion of Arbimectin in the treatment regimen for various forms of calcivirus significantly increases the percentage of recovery, with the exception of the nervous form, in which the drug is not effective. Thus, Arbimectin is recommended for use in complex therapy of feline calcivirus to improve its outcomes.
Zaykovskaya, O. Use of the antiviral drug «arbimectin» in the treatment regimen for calicivirus in cats / O. Zaykovskaya, A. Zhexenayeva, M. Zhakiyanova. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - № 4-1 (77). - Р. 95-102 (Uralsk).
Keywords: Feline calcivirus; Arbimectin; therapy; complex use; effectiveness; научный журнал; зкату